The development of a novel AND logic based fluorescence probe for the detection of peroxynitrite and GSH. Issue 15 (19th March 2018) - Sedgwick, Adam C.; Han, Hai-Hao; Gardiner, Jordan E.; Bull, Steven D.; He, Xiao-Peng; James, Tony D.
Abstract : We have developed a novel AND logic based fluorescence probe for the simultaneous detection of ONOO − and GSH (GSH-PF3 ). Abstract : We have developed a novel AND logic based fluorescence probe for the simultaneous detection of ONOO − and GSH (GSH-PF3 ). TheGSH-PF3 probe was synthesised over three steps starting from commercially available fluorescein. The probe was constructed by attaching the GSH reactive motif, 2, 4-dinitrobenzenesulfonyl, to the previously reported boronate fluorescence based probe, PF3 .GSH-PF3 produced only a small fluorescence response towards the addition of GSH or ONOO − separately. However, when the probe was exposed to both analytes, there was a significant (40-fold) fluorescence enhancement.GSH-PF3 demonstrated an excellent selectivity towards both GSH and ONOO − . In cellular imaging experiments the probe was shown to be cell permeable with no 'turn-on' response observed for the addition of either GSH or ONOO − separately. However, in the presence of both analytes, a clear fluorescence response was observed in live cells.GSH-PF3 was further able to monitor the co-existence of metabolically produced ONOO − and GSH by exogenous stimulation.